Feasibility Assessment of Landslide Monitoring by Means of SAR Interferometry: A Case Study in the Ötztal Alps, Austria - Plank, Simon; Michael, Krautblatter; Thuro, Kurosch (Springer, 2015)
Permafrost is degrading in high alpine areas, presumably due to global warming. This causes instabilities of slopes in mountainous areas. Differential synthetic aperture radar interferometry (D-InSAR) is a promising remote sensing technique which enables accuracies of millimeters for landslide monitoring over large areas. However, the following factors complicate its application. The specific imaging geometry of radar systems causes several distortions in SAR images of areas with topographic relief (shadowing and layover of radar responses). These effects deteriorate the application of InSAR. Advanced D-InSAR techniques, such as the persistent scatterer interferometry (PSI) require a stack of at least 15–50 SAR images. This makes its processing very time-consuming and expensive. Precondition of successful PSI application is a high enough number of persistent scatterers (PS) at which the deformation of the ground is analyzed. Here, exemplified for a case study in the Ötztal Alps, Austria, we present the application of lowcost methods enabling objective pre-survey suitability evaluation of D-InSAR—prior to recording of the area of interest (AOI). This feasibility assessment includes (a) the simulation of layover and shadowing areas (to determine the best suited imaging geometry to monitor a certain landslide) and (b) the estimation of PS based on freely available geodata (to test the applicability of PSI).